In-vitro comparison of anticancer activity between pure gallic acid and gallic acid - iron oxide coated with polyethylene glycol nanoparticles - Rosman, Raihana (2018)
Cancer poses one of the biggest health threats in the world. Lung cancer, breast cancer and colorectal cancer were the top three leading cause of cancer mortality worldwide, both in 2012 and 2015. Chemotherapy has been the most commonly used treatment to treat cancer but the side effects of conventional chemotherapy has proven to be detrimental to the body, as surrounding healthy normal cells are unnecessarily affected due to lack of selectivity, poor aqueous solubility and rapid degradation of the anticancer drug. This calls for a need of a safer anticancer drug and a more specific and sustained drug delivery system. Gallic acid is a bioactive polyphenol with anticancer and cytoprotective properties that can be found in plants and foods such as blueberries and walnuts. Polymeric magnetite nanoparticles, iron oxide-polyethylene glycol (FPEG), was used as a nanocarrier for gallic acid, synthesizing a gallic acid-iron oxide coated with PEG nanocomposite. This study compared the anticancer activity between pure gallic acid (GA) and the nanocomposite (FGPEG) to prove the significance of nanoparticles in ensuring a safer, bio-responsive and more efficient drug delivery. The 3-[4,5-methylthiazol-2-yl]-2,5-diphenyl-tetrazolium bromide (MTT) assay result showed that both GA and FGPEG exhibited time and dose-dependent cytotoxicity in human lung cancer cells (A549), human breast cancer cels (MCF-7) and human colon cancer cells (HT-29), while no cytotoxicity was seen in normal fibroblast cells (3T3). 3T3 has been one of the most widely used normal cell lines in anticancer studies. IC50 values caused by FGPEG were much lower in all cancer cell lines compared to those of GA alone. With the lowest IC50 value, HT-29 was the most responsive to FGPEG, followed by MCF-7 and A549. Acridine orange propidium iodide (AOPI) double staining showed that both GA and FGPEG were found to trigger morphological features related to apoptosis such as membrane blebbing, chromatin condensation and nuclei fragmentation. FGPEG treated cells showed distinctive morphological changes and higher rate of apoptosis than cells treated with GA, evident by the increased cell blebbing and the yellowish orange stained cells indicating late apoptosis. High resolution transmission electron microscopy (HRTEM) revealed intact cell membrane and nucleus, chromatin condensation, increased vacuolation, dilated mitochondria, elongated rough endoplasmic reticulum and nuclear shrinkage in both GA and FGPEG treated cells. However, the presence of autophagosomes, residual bodies, increased number of dilated organelles and lipid droplets seen only in FGPEG treated cells indicated cells were in late apoptosis progressing to secondary necrosis. Since FGPEG treated cells have displayed more distinguishable morphological characteristics stipulating higher rate of apoptosis than GA alone despite being subjected to the exact same prolonged in vitro conditions, the significant advantage of nanoparticles FPEG as a nanocarrier was evident. Our results demonstrated that polymeric magnetite nanoparticles are indeed advantageous over pure drug alone in anticancer drug delivery system, forming a compelling justification for the utilization of this design as a platform for a safer, more specific and sustained chemotherapeutic drug delivery.